MARKET BASKET ANALYSIS DENGAN ALGORITMA APRIORI PADA JACK'S MART - Naomi, Cathrine; Elisa, Erlin (Computer Science and Industrial Engineering, 2022)
The emergence of the Covid-19 vaccine currently brings major changes to the growth of the retail business in 2021 where the retail business is more developed and has improved better than the previous year. The more rapidly the minimarket is developing, the tighter the competition between minimarket entrepreneurs, so they are required to find a strategy that can increase sales. The mini market that is competing in Batam at this time is Jack's Mart. Jack's Mart is currently experiencing an increase in sales due to its location close to the SP Square, which makes this store often visited by consumers. The problem that arises at this time is that Jack's mart has not utilized transaction data during consumer buying and selling activities, in addition, the placement of goods in the store is also not in accordance with consumer behavior. To overcome this problem, data mining can be applied with the Market Basket Analysis method which aims to find products purchased by consumers simultaneously. The results in this study found the highest position products, namely mineral water, Snacks, and Soft Drinks with 33,33% Support and 100,00% confidence.